E06 The effect of programmed resistance training on the muscle myofibrillar proteome - Rudhun, Lihnam Martina; Aaron, Thomas; Stead, Connor; Hesketh, Stuart; Sutherland, Hazel; Burniston, Jatin; Jarvis, Johnathan (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Resistance training increases muscle size but little is known about the dynamic processes that underpin the gains in muscle mass. We investigated rat muscle during 30 days of unilateral programmed resistance training (PRT) using the stable isotope (deuterium oxide; D2O) in vivo and proteomics. Three-month-old, male Wistar rats (body weight 348 ± 20 g) were assigned to four groups (n = 4, in each), including a control group and experimental groups that received D2O for 10, 20 or 30 days. Under ethically approved procedures, deuterium was administered, and a stimulating device was surgically implanted to activate the left peroneal nerve and cause maximal contraction of the dorsiflexors (inc. tibialis anterior; TA) and partial contraction of the plantar flexors. PRT consisted of 1 bout per day of 5 sets of 10 repetitions (1 repetition consisted of 2 s stimulation at 100 Hz with 2 s rest between repetitions and 2.5 min between sets). One hour after the final training bout (i.e. day 10, 20, or 30) animals were killed and the left (stimulated) and right (contralateral control) TA were extracted and weighed. Muscles were fractionated into myofibrillar and sarcoplasmic components. Protein content was calculated via Bradford assay and proteomic analysis of myofibrillar proteins was conducted via liquid chromatography-tandem mass spectrometry of peptide digests. Statistical analysis was conducted using R (v4.3.2.) and functional annotation was performed using the STRING database. Two-way mixed ANOVA was used to investigate differences between condition (stimulated vs contralateral control) and time (0, 10, 20, or 30 days). The protein content of stimulated TA increased (P < 0.05) from 0.579 ± 0.05 mg at day zero to 1.096 ± 0.15 mg after 30 days of PRT, whereas the protein content of control TA (0.618 ± 0.04 mg) was consistent across the 30-day experimental period. Proteomic analysis encompassed 244 proteins and the abundance of 45 proteins exhibited a significant (P < 0.05) interaction between condition and time. Stimulated muscle was enriched in mitochondrial enzymes. For example, the beta-subunit of ATPase synthase (ATPB) increased from 14.6 ± 4.5 to 74 ± 15.6 μg in stimulated TA and was 17 ± 5 in control TA. PRT also increased the abundance of neonatal myosin heavy chain (MYH8), four-and-a-half LIM domains protein 1 (FHL1) and muscular LMNA interacting protein (MLIP). These findings suggest the energy requirements of daily PRT are met by mitochondrial metabolism and PRT may be associated with activation of the muscle developmental programme.